The Application Of Boiled Bay Leaf Water In Reducing Uric Acid Levels And Pain Intensity Using Betty Neuman’s Theory Model In The Working AreaOf Jembatan Kecil Public Health Center, Bengkulu City, 2025 - Yugita, Ira; Aprianti , Delta (Utami Publisher, 2026)
Increased uric acid levels are a common health problem experienced by the community, particularly among older adults, and can lead to joint pain. One of the non-pharmacological therapies used to reduce uric acid levels is the administration of boiled bay leaf water. This study aims to determine the effectiveness of boiled bay leaf water in reducing uric acid levels and pain intensity in patients with gout arthritis by applying Betty Neuman’s nursing model.This research used a case study design involving two participants aged over 40 years who were diagnosed with gout arthritis. The intervention was carried out for three days with the administration of boiled bay leaf water twice daily. The instruments used included a pain scale observation sheet and recorded uric acid levels.The results showed that after the intervention, there was a decrease in pain scale in both participants from moderate to mild levels (from scale 5 → 1 and 6 → 2). The intervention also demonstrated an adaptive response in improving patient coping based on Betty Neuman’s theory.The conclusion of this study is that boiled bay leaf water is effective in reducing pain intensity among patients with gout arthritis and may serve as a complementary therapy. It is recommended that patients continue this therapy independently as a preventive measure against recurrent pain.